Effects of Red Blood Cell Distribution Width on the Outcomes of Patients with Sepsis in Intensive Care Unit: A Retrospective Study - Burhan Sami Kalın; İhsan Solmaz (Galenos Yayinevi, 2022)
Objective:This study aimed to determine the prognostic value of red cell distribution width (RDW) in patients with sepsis in intensive care unit (ICU).Materials and Methods:This single centre study includes a retrospective analysis of critically ill patients with sepsis. Patients' demographic data; comorbidities; RDW values upon ICU admission, day 3 (RDW3) and day 7 (RDW7); Acute Physiology and Chronic Health Evaluation-II (APACHE-II) score; need for haemodialysis and invasive mechanical ventilation (IMV) were compared between survivors and non-survivors. In addition, patients were divided into the following two groups: high RDW (>14.5%) and normal RDW (≤14.5%). Logistic regression analysis was performed to determine independent risk factors for ICU mortality.Results:A total of 102 patients with sepsis were included. Survivors had lower RDW than non-survivors (p<0.05 for RDW values upon ICU admission, RDW3 and RDW7). The APACHE-II score, presence of septic shock on ICU admission, need for IMV and mortality rate were higher in patients in the high RDW group than those in patients in the normal RDW group (for all p<0.05). In this study, the presence of septic shock on ICU admission, RDW3 value and need for IMV were found to be independent risk factors for mortality.Conclusion:In this study, RDW3 value was significantly associated with mortality in critically ill patients with sepsis and has an important value in predicting the prognosis of patients with sepsis in ICU.